2022
DOI: 10.1159/000521130
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation for Post-Traumatic Stress Disorder: A Review of the Experimental and Clinical Literature

Abstract: <b><i>Introduction:</i></b> Up to 30% of patients with post-traumatic stress disorder (PTSD), especially combat veterans, remain refractory to conventional treatment. For them, deep brain stimulation (DBS) has been suggested. Here, we review the literature on animal models of PTSD in which DBS has been used to treat PTSD-type behavior, and we review and discuss patient reports of DBS for PTSD. <b><i>Methods:</i></b> A broad search was performed to find experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 97 publications
1
9
0
Order By: Relevance
“…A study with a war veteran suffering with PTSD showed that DBS‐mediated stimulation of the basolateral nucleus of the amygdala reduced more than 37% the symptoms 136 . Similar results were obtained in a follow‐up study of same patient and another PTSD patient 137 . Another case study showed that DBS in medial prefrontal cortex/uncinate fasciculate caused full recovery of patient from PTSD symptoms 138 .…”
Section: Invasive Brain Stimulationsupporting
confidence: 57%
See 1 more Smart Citation
“…A study with a war veteran suffering with PTSD showed that DBS‐mediated stimulation of the basolateral nucleus of the amygdala reduced more than 37% the symptoms 136 . Similar results were obtained in a follow‐up study of same patient and another PTSD patient 137 . Another case study showed that DBS in medial prefrontal cortex/uncinate fasciculate caused full recovery of patient from PTSD symptoms 138 .…”
Section: Invasive Brain Stimulationsupporting
confidence: 57%
“… 136 Similar results were obtained in a follow‐up study of same patient and another PTSD patient. 137 Another case study showed that DBS in medial prefrontal cortex/uncinate fasciculate caused full recovery of patient from PTSD symptoms. 138 Beside these, there is no other study available in the literature on DBS treatment in PTSD patients.…”
Section: Invasive Brain Stimulationmentioning
confidence: 99%
“…None of these DBS targets, not even the first modern era DBS of Benabid et al [87], did result from animal experiment. Only three of the current human applications of DBS stemmed from prior work on animal: the lesioning of the STN in primate models of PD [88, 89] led to high-frequency DBS of the STN in human PD; the low-frequency stimulation of the pedunculopontine nucleus in monkey [90] led to attempts of low-frequency DBS in PD patients with freezing of gait; and the numerous works on DBS in rodent models of post-traumatic stress disorder (PTSD) led to a cautious trial of DBS of the basolateral amygdala in patients with PTSD [91, 92]. In fact, some of the serendipitous discoveries during human clinical DBS have led researchers in the opposite direction, that is, from bedside to bench.…”
Section: Modern Dbs Eramentioning
confidence: 99%
“…However, a substantial proportion of patients do not respond to treatment modalities, thus rendering them refractory. This incidence is markedly higher in defence personnel who have been through traumatic, life-altering experiences [ 2 ]. Out of all psychiatric disorders, PTSD shows the highest comorbidity rates.…”
Section: Introductionmentioning
confidence: 99%